Analisis Risiko yang Dihadapi pada Usaha Minyak Daun Cengkeh di Kelurahan Ulunggolaka Kecamatan Latambaga Kabupaten Kolaka - Nurfadilla S; Yusna Indarsyih; Weka Gusmiarty Abdullah; Edelwais Fatma (Universitas Galuh, 2026)
This study aims to identify risks, analyze risk levels, and evaluate risk management efforts in the clove leaf oil business in Ulunggolaka Village, Latambaga District, Kolaka Regency. A descriptive method with saturated sampling involving 20 respondents was employed. The results indicate that major risks include seasonal raw material availability, poor leaf quality, labor shortages, machine breakdowns, price fluctuations, and distribution constraints. Risk management strategies include raw material stockpiling, stricter sorting procedures, improved cooling techniques, and strengthening packaging quality and marketing networks.